2017
DOI: 10.1016/j.nuclphysa.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between event-by-event fluctuation measurements and theory predictions in relativistic nuclear collisions

Abstract: We develop methods to deal with non-dynamical contributions to event-by-event fluctuation measurements of net-particle numbers in relativistic nuclear collisions. These contributions arise from impact parameter fluctuations and from the requirement of overall net-baryon number or net-charge conservation and may mask the dynamical fluctuations of interest, such as those due to critical endpoints in the QCD phase diagram. Within a model of independent particle sources we derive formulae for net-particle fluctuat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 23 publications
7
157
2
Order By: Relevance
“…The analysis of experimental data was performed with the Identity Method [21][22][23][24][25]. Futhermore, based on the recently proposed model, it was demonstrated that non-dynamical fluctuations, such as those stemming from unavoidable fluctuations of participant nucleons are immaterial for the second cumulants of net-protons measured at LHC energies [18]. The obtained results for the second cumulants of net-protons, normalised to the Skellam baseline, are presented in the left panel of Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of experimental data was performed with the Identity Method [21][22][23][24][25]. Futhermore, based on the recently proposed model, it was demonstrated that non-dynamical fluctuations, such as those stemming from unavoidable fluctuations of participant nucleons are immaterial for the second cumulants of net-protons measured at LHC energies [18]. The obtained results for the second cumulants of net-protons, normalised to the Skellam baseline, are presented in the left panel of Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…It is argued that these deviations, as a functions of acceptance, are due to the global baryon conservation, which should be corrected for before comparison to theoretical calculations within GCE. For the second cumulants the contribution from the global baryon number conservation depends only on the acceptance factor α = n p / N 4π B with n p and N 4π B referring to the mean number of protons inside the acceptance and the mean number of baryons in the full phase space respectively [18]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] for second order cumulant, non-equilibrium effects near the critical point also lead to the violation of the locality assumption. Third, other various effects in real heavyion collisions [1,13,16,18,19] have also be taken into account. We left the inclusion of these effects for future study.…”
Section: Implications To Experimentsmentioning
confidence: 99%
“…In particular, the study of the non-Gaussianity of fluctuations is one of the central topics in this realm [7][8][9][10]. Active studies have been carried out theoretically [11][12][13][14][15][16][17][18][19][20][21][22][23], and experimentally by STAR and ALICE collaborations [24][25][26][27][28][29], as well as in the lattice QCD numerical simulations [30]. The fluctuation observables will also play crucial roles in the future heavy-ion experiments aiming at the study of extremely dense medium [31][32][33].…”
Section: Introductionmentioning
confidence: 99%